Rotation Speed Recovery Strategy Based On Variable Power Curve of Inertia Control from DFIG Wind Turbine. (October 2018) - Liu, R; Song, P; Wang, X S; Lin, Z W
Abstract: With the increase of wind power capacity incorporated into the grid, the permeability of wind power increases continuously, which leads to the reduction of the equivalent inertia of the system. A new strategy of recovering rotor speed that increases the output power by modifying the variable power curve is proposed in this paper, which decreases the drop of the active power. So as to reduce the secondary frequency dips caused by the sudden drop of the active power when the speed restores. The paper optimizes the secondary frequency dips by modifying the variable power curve continuously. This article simulates this strategy through setting up a system by Simulink. Compared with the traditional recovery strategy, validity of the proposed strategy is demonstrated through simulation and analysis.